The Grammatical and Mechanical Errors of Students in Essay Writing - Siti Yuliah; Agustia Widiastuti; Ghea Resta Meida (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2019)
This study is about an analysis of grammatical and mechanical errors made by the students across the three levels of writing ability: high, average, and low. The grammatical and mechanical aspects analyzed were subject-verb agreement, sentence fragment, conjunction, capitalization, punctuation, and spelling. The present study aimed to find out the most common grammatical and mechanical errors and to identify the percentage of each error found in the essays. Students’ essays taken from their English writing quiz were collected as the data since they might contain grammatical and mechanical errors. This study employed textual analysis and was supported by simple calculation to determine the frequency of each error found. The data were analyzed by identifying the errors, explaining why the errors are incorrect and writing the proper corrections, and evaluating the errors to get the percentage of each error found. The results showed that the most common grammatical error found is the use of conjunction, that is around 20.6%, and the most common mechanical error found is punctuation by around 21.6%.